Monday's troll : poems - Prelutsky, Jack.; Sis, Peter (New York : Greenwillow, 1996)
A collection of seventeen poems about such unsavory characters as witches, ogres, wizards, trolls, giants, a yeti, and seven grubby goblins.
6.8
3-6
3-6
Wilson's Children
Elem. School Library Collection
School Library Journal starred
Keywords: Children's poetry, American; Witchcraft -- Juvenile poetry; Wizards -- Juvenile poetry; Fairies -- Juvenile poetry; American poetry; Supernatural -- Poetry; Witchcraft -- Poetry; Wizards -- Poetry; Fairies -- Poetry; Supernatural -- Poetry